Nematode parasites infecting the starry batfish Halieutaea stellata (Vahl) (Lophiiformes: Ogcocephalidae) from the East and South China Sea. Issue 5 (27th April 2015) - Li, L; Zhao, W‐T; Guo, Y‐N; Zhang, L‐P
Abstract: The starry batfish Halieutaea stellata (Vahl) is a small, benthic fish found in Indo‐West Pacific Oceans. However, our present knowledge of the helminth parasites of this fish is still fragmentary. In this study, a total of 29 fish collected from the East and South China Sea were examined to determine the prevalence, intensity and species composition of helminth parasites in H. stellata . Using morphological and molecular approaches, four species of nematodes were found parasitic in this fish host, including the adults and fourth‐stage larvae of Raphidascaroides nipponensis Yamaguti 1941; adults and third‐stage larvae of Raphidascaris lophii (Wu 1949), third‐ and fourth‐stage larvae of Hysterothylacium larval type IV‐A of Shamsi, Gasser & Beveridge 2013 and third‐stage larvae of Hysterothylacium amoyense (Hsü 1993). Halieutaea stellata represents a new host record for the three last‐named nematodes. Raphidascaroides nipponensis with the highest prevalence (82.5%) and intensity (mean = 13.5) of infection was considered as the dominant parasite species in H. stellata . The detailed morphology of the different developmental stages of the four nematode species was studied using light and scanning electron microscopy. All nematode species were also genetically characterized by sequencing and analysing the internal transcribed spacer (ITS) of the ribosomal DNA. This study provides further data on the occurrence of nematode parasites in H. stellata and also contributes to facilitate an accurate and rapid diagnosis of the infection by these little‐known nematodes.